Uso da linguagem de programação Python na formação de professor para o ensino de matemática - Carneiro, Silas dos Santos (2022)
This article was the result of a TCC developed to obtain the degree of Licentiate in Mathematics by the University of Amazon State, being of qualitative nature and with the main objective of demonstrating that the Python programming language can be used in teaching as auxiliary tool in Mathematics classes. As work methodology, we started with a research of the curriculum of mathematics courses in 30 Brazilian universities (Federal and State) to obtain information that the subject “Programming Language” was part of these curriculums. We also carried out studies with Python to develop programs that were easy to understand and that would allow working with mathematical subjects. As a result of this study, we made applications of this language in topics such as: matrix, functions and graphs. With this, we present the possibility of using a programming language as a teaching tool.